Violência urbana e medo do crime: efeitos psicológicos em profissionais da saúde - Eleutério, Filipe Mourão (2023)
Violence is a complex phenomenon that affects Brazil and has a major impact on public policies. Especially in urban centers, it impacts the performance of health policies and population access. Mental illness and exposure to urban violence are related, and depressive, anxious and diffuse conditions may appear. Furthermore, high levels of fear of crime are observed in urban populations, associated with mental health problems. In Fortaleza, Primary Health Care teams live with high levels of violent crime and the activities of non-state armed groups seeking to control territories. The municipality uses Acesso Mais Seguro (AMS), from the International Committee of the Red Cross (ICRC), the main intervention strategy underway in the country. In this context, this dissertation had the general objective of evaluating the psychological effects of exposure to urban violence on Primary Health Care (PHC) professionals. More specifically, we expected to: a) analyze the prevalence of exposure to urban violence among professionals in the sample; b) measure the subjective impact of urban violence on the mental health of Primary Health Care workers; and c) investigate the effect of participating in Acesso Mais Seguro on the mental health of the sample. The research sought to investigate the variables anxiety, depression, stress and fear of crime. To this end, the following instruments were used: Depression, Anxiety and Stress Scale (DASS), Gorman-Smith and collaborators’ (2000) and Etopio and Berthelot’s (2022) Fear of Crime Scales and sociodemographic questionnaire. The design consisted of an exploratory study and included a non-probabilistic sample of 465 professionals including community health agents, nurses, nursing technicians and doctors from Primary Care in Fortaleza. The data found demonstrated that the sample had a high prevalence of exposure to urban violence. Exposure correlated with an important subjective impact, mainly due to worse mental health indicators and fear of crime in specific groups: workers who experienced multiple forms of violence at work; people undergoing psychological or psychiatric care; people with a family history of mental disorder. Although having received the AMS training proved to be a protective factor, being part of the Decision-Making Group (GTD) correlated with higher levels of stress. The study was able to contribute with evidence of the need for both preventive and after exposure interventions towards this public. More studies are suggested focused on the problems experienced by health professionals who work in violent contexts and the implementation and assimilation of AMS in the field of public policies.